Impact and compression after impact response in thin laminates of spread-tow woven and non-crimp fabrics. (1st May 2019) - Sasikumar, A.; Trias, D.; Costa, J.; Blanco, N.; Orr, J.; Linde, P.
Abstract: Recent research has been devoted to thin laminates as a result of aeronautic industries shifting to thinner and lighter structures. In an attempt to improve the out-of-plane response and reduce manufacturing costs considerably, airplane manufacturers are exploring (apart from unidirectional tapes) textile fabrics of different fabric architectures. Within the framework of thin laminates, this paper investigates the impact and compression after impact (CAI) of two types of aerospace graded spread-tow fabrics, namely non-crimp fabrics and woven fabrics, where stitching and weaving, respectively, govern the architecture. The study also comprises two different ply thicknesses (thin and intermediate ply grades) for both fabrics. Experimental results reveal that while woven fabrics display higher damage resistance, non-crimp fabrics ensure higher damage tolerance. The intermediate ply grade performed better than thin plies in terms of damage resistance and CAI strength for both fabrics, as thin ply non-crimp fabric laminates exhibited early and extensive fibre damage.